Organizational Symmetry and its Relationship to Job Happiness / A Survey Study of the Opinions of a Sample of Workers in The Office of the Ministry of Agriculture and Water Resources in the Kurdistan Region (NTU journal for Administrative and Human Sciences (JAHS), 2023)
Achieving pleasure and satisfaction for working individuals as a result of their obtaining material and moral benefits and stability from their work requires the presence of organizational symmetry, which is based on the presence of feelings of psychological and social belonging by the working individuals to the organizations in which they work and their feeling that they are an integral part of the organization, as the current research aims to Statement of the role and impact played by organizational similarity on job happiness among workers in the office of the Ministry of Agriculture and Water Resources in the Kurdistan region, and to identify the availability of research variables and its dimensions in the field researched. The questionnaire as a main tool for data collection, where (100) questionnaire forms were distributed, of which (97) forms were retrieved valid for analysis. It has been reached that the hypotheses obtained by the research, which indicate the existence of a correlation relationship, are valid There is a significant difference between organizational symmetry represented by its dimensions and functional happiness represented by its dimensions.